2001
DOI: 10.1001/jama.285.22.2859
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between the T29→C Polymorphism in the Transforming Growth Factor β1 Gene and Breast Cancer Among Elderly White Women

Abstract: Our findings suggest that TGF-beta1 genotype is associated with risk of breast cancer in white women aged 65 years or older. Because the T allele is the common variant and confers an increased risk, it may be associated with a large proportion of breast cancer cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 21 publications
3
95
6
Order By: Relevance
“…In contrast with previous results, [17][18][19][20][21]36 we did not find a significant difference in plasma levels of TGF-β1 depending on codon 10 genotype in either patients or donors. This lack of effect may be due to the fact that the subjects did not have a homogenous state of immune activation (donors were in a resting state and patients were under different conditions depending on the stage of disease, or recent chemotherapy).…”
Section: Ii-iv (%) Iii-iv (%)contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with previous results, [17][18][19][20][21]36 we did not find a significant difference in plasma levels of TGF-β1 depending on codon 10 genotype in either patients or donors. This lack of effect may be due to the fact that the subjects did not have a homogenous state of immune activation (donors were in a resting state and patients were under different conditions depending on the stage of disease, or recent chemotherapy).…”
Section: Ii-iv (%) Iii-iv (%)contrasting
confidence: 99%
“…While codon 25 SNP have been consistently associated with decreased plasma levels, 17,18 conflicting data have been published regarding the impact of codon 10 SNP on plasma levels of TGF-β1. [17][18][19][20][21][22] These polymorphisms have been associated with an increased incidence of breast and colorectal neoplasia 20,23 and worse outcome following solid organ transplantation 24 and sibling HSCT. 5,25,26 To date there is no published evidence on the possible role of these SNP in unrelated donor HSCT, or on plasma TGF-β1 levels and clinical outcomes following transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study involving 3075 women aged 65 years or older, Ziv et al (12) reported that subjects with the C/C TGF-␤ 1 genotype had a 64% reduced risk of developing breast cancer as compared with women with the C/T or T/T genotype. Results from a recent report of three case-control series of 3987 cases and 3867 controls confirmed that the T/T genotype was related to an increased risk of invasive breast cancer, but that the magnitude of the risk was much smaller than in the earlier study (odds ratio, 1.21 for C/C versus T carrier; Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them were in the promoter region at positions G-800A and C-509T. Two were located within the signal peptide sequence in exon 1 at codon 10 (CTG3 CCG) and codon 25 (CGG3 CCG), resulting in changes in the amino acid sequences (Leu 10 3 Pro and Arg 25 3 Pro, respectively). The last one was Table III).…”
Section: Tgf-␤1mentioning
confidence: 99%
“…6 Several polymorphisms in the TGF-␤1 and its receptor genes have been reported. 9 -11 After functional considerations, we selected 5 polymorphisms in the TGF-␤1 gene (G-800A, C-509T, Leu 10 3 Pro, Arg 25 3 Pro and Thr 263 3 Ile), one polyalanine polymorphism in the TGF-␤RI gene (9A36A) and 2 polymorphisms in the TGF-␤RII gene (G-875A and A-364G) to carry out a case-control study. Our aim was to test whether the 8 selected polymorphisms on the TGF-␤ signaling pathway were associated with familial or unselected breast cancer.…”
mentioning
confidence: 99%